2021
DOI: 10.1111/1755-0998.13332
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐level genome of the mud crab (Scylla paramamosain estampador) provides insights into the evolution of chemical and light perception in this crustacean

Abstract: Mud crabs, found throughout the Indo‐Pacific region, are coastal species that are important fisheries resources in many tropical and subtropical Asian countries. Here, we present a chromosome‐level genome assembly of a mud crab (Scylla paramamosain). The genome is 1.55 Gb (contig N50 191 kb) in length and encodes 17,821 proteins. The heterozygosity of the assembled genome was estimated to be 0.47%. Effective population size analysis suggested that an initial large population size of this species was maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 117 publications
(150 reference statements)
1
26
0
Order By: Relevance
“…These features match the findings from the CHH1 genes of P. trituberculatus and E. sinensis in this study. However, we did not identify CHH1 genomic sequences in the S. paramamosain genome, which might be attributed to incomplete genomic assembly (Zhao et al, 2021). There are three indications suggesting that the Sp-CHH1 gene has four exons and generates two splice variants.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These features match the findings from the CHH1 genes of P. trituberculatus and E. sinensis in this study. However, we did not identify CHH1 genomic sequences in the S. paramamosain genome, which might be attributed to incomplete genomic assembly (Zhao et al, 2021). There are three indications suggesting that the Sp-CHH1 gene has four exons and generates two splice variants.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, due to advances in sequencing technologies, several decapod genomes have been sequenced and assembled (Gutekunst et al, 2018;Zhang et al, 2019;Tan et al, 2020;Tang et al, 2020Tang et al, , 2021Van Quyen et al, 2020;Cui et al, 2021;Uengwetwanit et al, 2021;Zhao et al, 2021), providing an important basis for comprehensive understanding and differentiation of decapod CHHs and their putative receptors, as well as for further exploration of CHHs genomic structures and characteristics. In this study, CHHs and their putative GPCRs were identified and characterized in three species of economically important crabs: the mud crab, Scylla paramamosain, P. trituberculatus, and the Chinese mitten crab, Eriocheir sinensis.…”
Section: Introductionmentioning
confidence: 99%
“…The selected genes were those encoding hepatocyte nuclear factor 4 (HNF4), carnitine palmitoyl transferase (CPT), very-long-chain acyl-CoA dehydrogenase (VLCAD), palmitoyl protein thioesterase (PPT) and 3-ketoacyl-CoA thiolase (KAT). Table 1 shows the primers used according to genome study ( 46 ). Three replicates were prepared for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…[98] It is only within the last year that high-quality genomic resources have become available for meiurans, though only for carcinized members. Two species of eubrachyuran, Portunus trituberculatus, [107,108] and Scylla paramamosain [109] (both members of the same family), and one species of king crab, Paralithodes platypus [110] now have published chromosome-level genome assemblies. The eubrachyuran Eriocheir japonica sinensis also has a recently updated genome assembly.…”
Section: Towards Predicting the Evolution Of Crabsmentioning
confidence: 99%